2013
DOI: 10.1371/journal.pone.0077473
|View full text |Cite
|
Sign up to set email alerts
|

The Suppressive Role and Aberrent Promoter Methylation of BTG3 in the Progression of Hepatocellular Carcinoma

Abstract: BackgroundBTG3 (B-cell translocation gene 3) has been identified as a tumor suppressor and hypermethylation contributes to its down-regulation in some tumors, but its role in hepatocellular carcinoma (HCC) remain unknown. This study aimed to detect the expression and methylation status of BTG3 in HCC cell lines or tissues, and determine its function in HCC progression.MethodologyThe expression of BTG3 was detected in HCC cell lines and HCC tissue by real-time RT-PCR, Western blot or immunohistochemistry. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…In addition, we demonstrated that BTG3 obviously decreased the migratory and invasive abilities of GC cells in vitro. Decreased expression of BTG3 is linked to carcinogenesis and aggressiveness of ovarian cancer and hepatocellular cancer (Lv et al 2013;Deng et al 2013). Therefore, the above results provide evidence that BTG3 can function as a suppressor in the progression of GC.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In addition, we demonstrated that BTG3 obviously decreased the migratory and invasive abilities of GC cells in vitro. Decreased expression of BTG3 is linked to carcinogenesis and aggressiveness of ovarian cancer and hepatocellular cancer (Lv et al 2013;Deng et al 2013). Therefore, the above results provide evidence that BTG3 can function as a suppressor in the progression of GC.…”
Section: Discussionmentioning
confidence: 73%
“…Recently, several studies have shown that BTG3 was associated with tumorigenesis. It has been reported as a tumor suppressor in several tumor types (Majid et al 2009(Majid et al , 2010Yu et al 2008;Lv et al 2013;Chen et al 2013). However, the expression pattern and function of BTG3 in the progression of GC remain elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence has shown that BTG3 expression is associated with tumorigenesis and serves as a candidate tumor suppressor gene in various cancers [45-47]. As reported, BTG3 involves in the suppression of proliferation, cell cycle progression and metastasis [48-51]. However, the association between BTG3 and miRNA has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…These results strongly suggest that miR-93 directly binds to the predicted BTG3 3 0 -UTR site and accelerates BTG3 mRNA degradation. Of note, the observed downregulation of BTG3 in ESC may only cause in part by miR-93, as the promoter region of BTG3 is known to be hypermethylated in several human cancers, which also contributes to downregulation of BTG mRNA [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%